Apolipoprotein A‐I in mouse cerebrospinal fluid derives from the liver and intestine via plasma high‐density lipoproteins assembled by ABCA1 and LCAT. Issue 6 (20th October 2020) - Tsujita, Maki; Vaisman, Boris; Chengyu, Liu; Vickers, Kasey C.; Okuhira, Kei‐ichiro; Braesch‐Andersen, Sten; Remaley, Alan T.
Abstract : Apolipoprotein (apo) A‐I, the major structural protein of high‐density lipoprotein (HDL), is present in human and mouse cerebrospinal fluid (CSF) despite its lack of expression in brain cells. To identify the origin of apoA‐I in CSF, we generated intestine‐specific and liver‐specific Apoa1 knockout mice ( Apoa1 ΔInt and Apoa1 Δliv mice, respectively). Lipoprotein profiles of Apoa1 ΔInt and Apoa1 ΔLiv mice resembled those of control littermates, whereas knockout of Apoa1 in both intestine and liver ( Apoa1 ΔIntΔLiv ) resulted in a 60‐percent decrease in HDL‐cholesterol levels, thus strongly mimicking the Apoa1 −/− mice. Immunoassays revealed that mouse apoA‐I was not present in the CSF of the Apoa1 ΔIntΔLiv mice. Furthermore, apoA‐I levels in CSF were highly correlated with plasma spherical HDL levels, which were regulated by ABCA1 and LCAT. Collectively, these results suggest that apoA‐I protein in CSF originates in liver and small intestine and is taken up from the plasma. Abstract :